Quantifying the relative amount of mouse and human DNA in cancer xenografts using species-specific variation in gene length. (March 2010) - Lin, Ming-Tseh; Tseng, Li-Hui; Kamiyama, Hirohiko; Kamiyama, Mihoko; Lim, Phillip; Hidalgo, Manuel; Wheelan, Sarah; Eshleman, James R.
Human cancer cell lines and xenografts are valuable samples for whole-genome sequencing of human cancer. Tumors can be maintained by serial xenografting in athymic (nude) or severe combined immunodeficient (SCID) mice. In the current study, we developed a molecular assay to quantify the relative contributions of human and mouse in mixed DNA samples. The assay was designed based on deletion/insertion variation between human and mouse genomes. The percentage of mouse DNA was calculated according to the relative peak heights of PCR products analyzed by capillary electrophoresis. Three markers from chromosomes 9 and 10 accurately predicted the mouse genome ratio and were combined into a multiplex PCR reaction. We used the assay to quantify the relative DNA amounts of 93 mouse xenografts used for a recently reported integrated genomic analysis of human pancreatic cancer. Of the 93 xenografts, the mean percentage of contaminating mouse DNA was 47%, ranging from 17% to 73%, with 43% of samples having >50% mouse DNA. We then comprehensively compared the human and mouse genomes to identify 370 additional candidate gene loci demonstrating human-mouse length variation. With increasing whole-genome sequencing of human cancers, this assay should be useful to monitor strategies to enrich human cancer cells from mixed human-mouse cell xenografts. Finally, we discuss how contaminating mouse DNA affects next-generation DNA sequencing.